2018
DOI: 10.5194/amt-11-1757-2018
|View full text |Cite
|
Sign up to set email alerts
|

The NASA Carbon Airborne Flux Experiment (CARAFE): instrumentation and methodology

Abstract: Abstract. The exchange of trace gases between the Earth's surface and atmosphere strongly influences atmospheric composition. Airborne eddy covariance can quantify surface fluxes at local to regional scales (1-1000 km), potentially helping to bridge gaps between top-down and bottomup flux estimates and offering novel insights into biophysical and biogeochemical processes. The NASA Carbon Airborne Flux Experiment (CARAFE) utilizes the NASA C-23 Sherpa aircraft with a suite of commercial and custom instrumentati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 87 publications
(119 reference statements)
2
34
0
Order By: Relevance
“…All three show too much HF noise to resolve the inertial subrange of turbulence. Similar results are shown by Wolfe et al (2018) from low-level airborne carbon flux measurements over Maryland and Virginia. Beyond about 5 Hz (corresponding to 12 m horizontal distance at the typical airspeed of 60 m s −1 ) spectral drop-off due to dampening in the tubing is visible.…”
Section: Spectral Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…All three show too much HF noise to resolve the inertial subrange of turbulence. Similar results are shown by Wolfe et al (2018) from low-level airborne carbon flux measurements over Maryland and Virginia. Beyond about 5 Hz (corresponding to 12 m horizontal distance at the typical airspeed of 60 m s −1 ) spectral drop-off due to dampening in the tubing is visible.…”
Section: Spectral Analysissupporting
confidence: 83%
“…We performed coherency and correlation analysis with spectral resolution and as integral statistics and could not find any correlation between pressure and the CH 4 signal. Also Wolfe et al (2018) reported no pressure effect on the CH 4 signal from an airborne LGR analyser.…”
Section: Methane Analysermentioning
confidence: 96%
See 1 more Smart Citation
“…Although some effort is made to capture subgrid variability by combining tower clusters (e.g., IMN, BON) and similar ecosystems (e.g., Figure 2) and by examining sensitivity to spatial resolution (e.g., Fig-ure S1), we caution that spatial representativeness issues remain in the flux tower-model comparisons. Airborne eddy covariance surveys provide a viable option to increase footprint size toward regional scale (Wolfe et al, 2018); (iii) flux partitioning of eddy covariance NEE into GPP and TER also carries large uncertainties and can yield very different results depending on method (e.g., Figure S1). This uncertainty in itself may explain the short time lags between thaw and GPP observed at Bonanza Creek.…”
Section: Limitations and Uncertainties For Eddy Covariance Observatmentioning
confidence: 99%
“…Airborne eddy covariance (EC) provides neardirect measurements of surface-atmosphere exchange over landscape-to-regional scales (e.g. Lenschow et al 1981, Desjardins et al 1982, 1989, Crawford et al 1996, Sellers et al 1997, Gioli et al 2004, Sayres et al 2017, Wolfe et al 2018. Such observations have successfully been used to evaluate CH 4 emissions inventories (Hiller et al 2014) and to scale up tower-or aircraft-based fluxes via empirically-derived environmental response functions (Miglietta et al 2007, Metzger et al 2013, Zulueta et al 2013.…”
Section: Introductionmentioning
confidence: 99%